Vous êtes sur la page 1sur 5

-1 :

f . I F f I :
F . I
)F '( x) = f ( x
x : I
:
-1
:

F ( x ) = x2 + x + 1
F '( x) = 2 x + 1

: F f :

f ( x) = 2 x + 1

-2 :
f ( x) = 2
-a

\ F ( x) = 2 x + C / C
-b

f ( x) = x
1 2
x + C
2

-c

f ( x ) = x3
1 4
x + C
4

-d

= )F ( x

= )F ( x

*` / n

f ( x ) = xn

1
x n +1 + C
n +1

= )F ( x

-e

}f ( x ) = x r ; r `* {1

-f

1
x r +1 + C
r +1
f ( x) = x

= )F ( x

= x2
2 32
x + Cte
3
-g

)(2 x
+ Cte

)+ 1
4

= )F ( x
2

(x

)+ 1

1
u r +1 + C
r +1

(x

= )f ( x
1
4

= )F ( x

ur u ' :

-2 :
f .
F f I f I :
F +
\ .

:
F f I .

+ )' = F ' = f

(F

F + f . I
:
: f I . F +
-3 :
f . I
x0 I y0 \ . y0
F f . I
:

F ( x0 ) = y0

:
f . F ( x0 ) = y0

f ( x) = x + 1

-1

1 2
x + x + C = 1
2
F ( 2) = 1

:
:

= )F ( x

1 2
x + x + C = 1
2
2 + 2 + C = 1
C = 3

:
:
2
x + 1

-2

F ( 2) = 1

F ( 0) = 0

= )f ( x

F ( x ) = 2 Arc tan x + C

F ( 0) = 0

C = 0
= 2 Arc tan x

:
:

)F ( x

f ( x ) = cos 2 x

-3
:

:
:

+ C

)(2 x


F = 0
2
C = 0


F = 0
2
1
= )F ( x
sin
2

1
sin 2 x
2

= )F ( x

-4 :
F f . I
G g . I
: F + G f + g . I

-5 :
I .
:

F G f I
F G =
:
-6 :
f

) F (

x+C

1 2
x +C
2

xn

1 n +1
x +C
n +1

`n

xr

1 r +1
x +C
r +1

}r _ {1

' un u

1 n +1
u +C
n +1

`n

' ur u

1 r +1
u +C
r +1

}r _ {1

1
x +1

Arc tan x + C

cos x

sin x + C

sin x

cos x + C

) cos ( ax + b

1
sin ( ax + b ) + C
a

a0

) sin ( ax + b

1
cos ( ax + b ) + C
a

a0

1
cos 2 x

= ) 1 + tan 2 ( x

tan x + C

\ C

+ k

:
: f
x2 1
x2 + 1

f ( x) =

-1

x2 + 1 2
x2 + 1

2
+ 1
x + 1
2

F ( x ) = x 2 Arc tan x + C
f ( x) = x

x2 + 1

-2

1
2 x 3 x2 + 1
2
1
1
2
3
=
x
+
1
(2 x)
(
)
2

f ( x) =

1
2

F ( x) =

( x2 + 1) 3

1
1
+1
3

1
3

3
4

(x

3
8

(x

+ 1) 3

F ( x) =

3
8

=
F ( x) =

x2 + 1

+ 1)

(x

+ x + 3) 2

2
3

x2 + x + 3
1

(2 x

-3

+ 1)

( x 2 + x + 3) 2
f ( x) =

sin 3 x
cos5 x

F ( x ) = tan 3 x
=
f ( x) =

+ 1) 3

(2 x
2

+1

f ( x) =

(x

+ 1) x
2

-4
1
cos 2 x

1
tan 4 x
4

-5

2
1
2
f ( x) =
( x + 1) 3 2 x
2
5
1 3
F ( x) =
x 2 + 1) 3 + C
(
2 5
5
3
=
x 2 + 1) 3 + C
(
10